PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA - Yolanda, Desinta Ayu (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out the influence of financial ratio significantly to the profit changes. The population in this research is Property and Real Estate industrial companies which are listed in the Indonesia Stock Exchange which publishes its financial report from 2008 to 2011. The sample collection technique is conducted by using purposive sampling, 17 companies samples in this research. The data analysis which is used in this research is the multiple linear regressions and hypothesis test which is conducted by applying 17th version SPSS software. This research uses four independent variables as the indicator of assessment influence company profit change which is performed by using Quick Ratio, Total Assets Turnover, Debt to Total Assets Ratio, Net Profit Margin. The result indicates that partially only Total Asset Turnover and Net Profit Margin which has significant influence to the profit changes, while Debt to Total Asset Ratio has significant negative influence to the profit changes while Quick ratio has no significant influence to the profit changes. But, simultaneously, Quick Ratio, Total Asset Turnover, Debt to Total Asset Ratio and Net Profit Margin has significant influence to the profit changesKeywords: Quick Ratio, Total Assets Turnover, Debt to Total Assets Ratio, Net Profit Margin, and Profit Changes.